CONCEPT MAP OF THE UNDERSTANDING AND DIRECTION OF PAI CURRICULUM DEVELOPMENT - Mohammad Nurul Yaqin; Nur Ali Yasin (Jurnal Ikhtibar Nusantara, 2025)
This study aims to examine the approach to developing the Islamic Religious Education (PAI) curriculum through a literature study method. The main focus of this study is to explore the basic principles and ideal direction of PAI curriculum development by examining written sources, such as books, scientific journals, and education policy documents. The results of the study indicate that the development of the PAI curriculum ideally integrates Islamic values, national educational philosophy, student developmental psychology, social demands, and advances in science and technology. The approach used is holistic, accommodating academic, social reconstruction, and humanistic approaches, so that the PAI curriculum is not only normative-theological, but also contextual and transformative.